Perancangan Sistem Informasi Manajemen Sumber Daya Manusia Pada PPSU Kelurahan Mangga Dua Selatan - Muhammad Dira Amirullah; Bernadus Gunawan Sudarsono; Iskandar Zulkarnain (FIKOM - Bung Karno University, 2023)
The Public Facilities and Infrastructure Handling Officer (PPSU) is one of the jobs given the responsibility to repair public facilities and infrastructure in the DKI Jakarta area. At present the data storage process for PPSU officers in determining work placement areas is still being carried out using paper media and other supporting equipment, so that in the current process errors often occur in the placement of PPSU officers' work areas. Based on these problems, this study discusses the Human Resources Management Information System for PPSU Officers. The system design method in this study uses the Unified Modeling Language (UML) method and the analysis method uses the waterfall method equipped with the PHP programming language and the use of the MySQL database.